The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11626-015-9940-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification of Rattus norvegicus immature cumulus-oocyte complexes using hyaluronic acid

Abstract: The aim of this study was to assess in vitro meiosis resumption and nuclear maturation of Rattus norvegicus oocytes after vitrification with different cryoprotective solutions. Cumulus-oocyte complexes (COCs) were exposed to an equilibration solution for 4 min placed in cryoprotective solutions for 1 min and vitrified in open pulled straws. Cryoprotective solutions were prepared with 15% ethylene glycol + 15% dimethyl sulfoxide + 0.5 M sucrose and different supplements, to form the following groups: G1, 20% fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“… Parisa Jamalzaei [ 222 ] 2020 A HAA composed of HA and ALG Mouse preantral follicles Promoted the development of preantral follicles and oocyte maturation in mice and enhanced estrogen secretion. L M G Paim [ 224 ] 2015 A vitrification solution with 1% hyaluronic acid The cumulus oocyte complex Improved the meiotic recovery rate and nuclear maturation rate of norvegicus oocytes. Somayeh Tavana [ 225 ] 2016 The HABH Ovariectomized rats Prevented or reduced early ischemia-induced follicular loss, promoted follicular survival and angiogenesis.…”
Section: Biomaterials For Ovarian Aging Therapymentioning
confidence: 99%
See 1 more Smart Citation
“… Parisa Jamalzaei [ 222 ] 2020 A HAA composed of HA and ALG Mouse preantral follicles Promoted the development of preantral follicles and oocyte maturation in mice and enhanced estrogen secretion. L M G Paim [ 224 ] 2015 A vitrification solution with 1% hyaluronic acid The cumulus oocyte complex Improved the meiotic recovery rate and nuclear maturation rate of norvegicus oocytes. Somayeh Tavana [ 225 ] 2016 The HABH Ovariectomized rats Prevented or reduced early ischemia-induced follicular loss, promoted follicular survival and angiogenesis.…”
Section: Biomaterials For Ovarian Aging Therapymentioning
confidence: 99%
“…Vitrification of embryos has been successful, while cryopreservation of oocytes has still failed to achieve the expected results [ 223 ]. Paim et al used a vitrification solution with 1% hyaluronic acid to freeze the cumulus oocyte complex (COC) for 7 days and then heated and matured it in vitro for 30 h [ 224 ]. The results showed that adding 1% hyaluronic acid to vitrified frozen solution could improve the meiotic recovery rate and nuclear maturation rate of Rattus norvegicus oocytes in vitro.…”
Section: Biomaterials For Ovarian Aging Therapymentioning
confidence: 99%